The Robustness of Preferences during a Crisis: The Case of Covid-19 - Paul Bokern; Jona Linde; Arno Riedl; Peter Werner (Center for Economic Studies and ifo Institute (CESifo), 2023)
We investigate how preferences have been affected by exposure to the COVID-19 crisis. Our main contributions are: first, our participant pool consists of a large general population sample; second, we elicited a wide range of preferences (risk, time, ambiguity, and social preferences) using different incentivized experimental tasks; third, we elicited preferences before the onset of the crises and in three additional waves during the crises over a time period of more than a year, allowing us to investigate both short-term and medium-term preference responses; fourth, besides the measurement of causal effects of the crisis, we also analyze within each wave during the crisis, how differential exposure to the crisis in the health and financial domain affects preferences. We find that preferences remain remarkably stable during the crisis. Comparing them before the start and during the crisis, we do not observe robust differences in any of the elicited preferences. Moreover, individual differences in the exposure to the crisis at best show only weak effects in the financial domain.
Keywords: C90; D01; 330; preference robustness; crisis; risk-; time-; ambiguity- and social preferences; Covid-19